The New Drugs in the Treatment of Hypertension and Resistant Hypertension: A Review of Therapies - Muras, Mateusz Szymon; Lorenc, Tomasz; Marcinkowski, Krzysztof; Michalik, Maciej; Mikszta, Natalia; Mikszta, Jakub; Marcinkowska, Julia (Quality in Sport, 2025)
Advancements in pharmacotherapy for hypertension (HTN) have led to the development of new drug classes and innovative supportive treatments. Aprocitentan, an endothelin receptor antagonist, has demonstrated promising effects in managing resistant hypertension, as evidenced by the PRECISION study [1]. Another notable innovation is firibastat, an aminopeptidase A inhibitor, which reduces the activity of the renin-angiotensin system by modulating angiotensin II conversion in the brain. Studies on firibastat suggest its potential in reducing blood pressure in primary hypertensive patients [2]. In the treatment of resistant HTN, newer forms of aldosterone inhibitors, such as esaxerenone, have shown greater selectivity compared to spironolactone, reducing the risk of side effects [3]. Additionally, baxdrostat, a potassium salt of aldosterone synthase inhibitor, decreases aldosterone production and improves blood pressure control [1]. Adjunctive therapies, including renal denervation and baroreceptor stimulation, are being investigated for their efficacy in reducing resistance to medication in patients with resistant HTN. Research suggests that these interventions may be particularly beneficial for patients who do not respond to standard pharmacological treatments [4]. Further research into these pharmacological and procedural therapies is crucial for optimizing hypertension management strategies.